(untitled) (Journal of Hama University, 2019)
Civilization is not only a set of structures, buildings and roads; it is also not just a gathering of human beings in one geographical place. But civilization is a real interaction between humans in the context of different interactive systems (Social, intellectual, economic, spiritual ...) and between man and place in an intellectual_ cultural_ social_ historical_ economic mixture. Accordingly, we can say that the ancestral architecture plays an essential role in highlighting the determinants of the current architecture (identity). Therefore, relevant thinkers and officials should take us to investigation and to the scientific survey of the architecture of the past. Theoretically, to work to stop and ban what is being done as a result of subversive operations (macro and micro) to prevent what exists in the economic and intellectual imbalance wich sometimes tries and sometimes manage to uproot this architecture in response to its self corruption within the general technical architectural corruption